Double-peaked supernovae - Orellana, Mariana Dominga (2021)
Through hydrodynamical ID simulations we explore two of the more promissing physical scenarios invoked to explain peculiar double-peaked supenovae. One consists of a double radioactive nickel distribution formed when some of this material is pushed out by a putative jet that is related to the supernova explosion. The other scenario has only outer nickel, but the main peak is powered by a newly born magnetar. We present the whole evolution of the bolometric light curve for a helium-rich progenitor. The main goal is to compare the resulting bolometric light curves and to confirm the fact that, for some parameters, the two peaks are clearly departed, being the latter a brigther and broader main peak.